Effects of Cricket and Fruit Fly Flour in Growth Media on Beauveria bassiana (Bals.) Vuill Pathogenicity Against Zeugodacus cucurbitae (Coquillet) Prepupae - Noni Rahmadhini; U'ud Uda Marlina; Suputa Suputa; Ramadhani Mahendra Kusuma (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2025)
Zeugodacus cucurbitae (Diptera: Tephritidae) is a major insect pest of horticultural crops, causing significant yield losses.The efficacy of Beauveria bassiana, a potential biocontrol agent, can be influenced by growth media composition. This study examined the effects of cricket and fruit fly flour on B. bassiana growth and pathogenicity against Z. cucurbitae. The methods added B. bassiana growth media with different concentrations (0%, 0.5%, 1%, and 1.5%) of cricket and fruit fly flour and assessing its pathogenicity against Z. cucurbitae at a spore density of 10⁶ and 10⁸ spores/mL. The results showed that 1% cricket flour combined with a spore density ofspores/mL resulted in the highest mortality rate (29.33%) and the fastest infection (2 days). The lowest average mortalities were found in treatments without flour addition which were 21.3%, 19.3%, and 19%, respectively. The longest time to cause infection was observed in 7 days. Infection symptoms are marked by the emergence of white fungal mycelia covering the cuticle, while infected adults exhibit deformed, wrinkled, and smaller wings. These findings highlight the potential of growth media optimization to enhance B. bassiana virulence, contributing to the development of more effective and sustainable biocontrol strategies against Z. cucurbitae.